2013
DOI: 10.1093/iwc/iwt061
|View full text |Cite
|
Sign up to set email alerts
|

Let'S Talk About Technology for Peace: A Systematic Assessment of Problem-Based Group Collaboration Around an Interactive Tabletop

Abstract: This work is concerned with the exploration of ideas in the realm of technology for peace, produced by small groups of students working around an interactive tabletop. A collaboration-enforcing tabletop application was used to mediate dialog and collaborative construction of a taxonomy of ideas based on the participants' consensus. The scenarios for discussion concerned the promotion of global peace and the social integration of immigrants in the society. The participants' dialog and interactions were video-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…This work has examined collaborations employing a variety of new technologies, including large multi-touch displays [1,27,38] and tabletops [7,24,39]. Other work has examined remote collaborations using these technologies, studying how distributed tabletops may support gesture use [17], how virtually embodying users' arms affects coordination on distributed tabletops [10], and how design guidelines for non-distributed tabletop settings may extend to distributed tabletops [26].…”
Section: Technological Support For Collaborationmentioning
confidence: 99%
“…This work has examined collaborations employing a variety of new technologies, including large multi-touch displays [1,27,38] and tabletops [7,24,39]. Other work has examined remote collaborations using these technologies, studying how distributed tabletops may support gesture use [17], how virtually embodying users' arms affects coordination on distributed tabletops [10], and how design guidelines for non-distributed tabletop settings may extend to distributed tabletops [26].…”
Section: Technological Support For Collaborationmentioning
confidence: 99%
“…In contrast to previous work (e.g. Ioannou et al 2013;Zancanaro et al 2012), the participants are not co-located and there is no human intervention for translation. The main goal of this paper is to demonstrate the feasibility of automated mediation between remote participants in order to guide them towards an effective interaction.…”
Section: Introductionmentioning
confidence: 87%
“…For example, studies on shared interactive spaces have shown that collaborative storytelling can be used to facilitate conflict resolution and to support mutual understanding between people with different cultures (Ioannou and Chrystalla, 2016;Zancanaro et al, 2012). These studies investigated the impact of technologysupported interventions for mitigating intergroup conflicts (Stock et al, 2008;Zancanaro et al, 2012), discussing problematic and controversial topics (Ioannou et al 2013;Ioannou and Chrystalla, 2016), learning about conflict management (Brynen and Milante, 2013) and reflecting on controversial historical events (Pollack and Kolikant, 2012).…”
Section: Digital and Collaborative Storytellingmentioning
confidence: 99%
“…There is already substantial work on using tabletops to support collaborative learning [30] [31]. There is also ev idence that tabletops can help address the above-mentioned issues, moving attention away from a single input device such as a mouse or keyboard [32], promoting equal participation and shared control [33]. Therefore, the present work points attention to surface computing as a technology that can expand the artifact ecology to provide further support for collaboration and learning.…”
Section: Affordances Of Artifact Ecology and Design Implicationsmentioning
confidence: 97%